The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/nu13103386
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Constipation: Is a Nutritional Approach Reasonable?

Abstract: Chronic constipation (CC) is one of the most common gastroenterological diagnoses in clinical practice. Treatment includes several steps, depending on the severity of symptoms. Lifestyle modifications and increased intake of fiber and water are suggested by most health professionals. Unfortunately, the recommendations in this regard are the most varied, often conflicting with each other and not always based on solid scientific arguments. This paper aims to clarify this topic by providing practical indications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Therefore, in routine clinical practice, dietary management is usually considered the cornerstone of any treatment for chronic constipation. Finite sample size and methods restrict the exploration of complex mechanisms linked to all kinds of foods, so current research mainly focuses on a small part of food ingredients, such as fiber and mineral water ( 5 ). Previous studies have confirmed that intake of low liquid, high dietary saturated fat would increase the constipation risk, while intake of soluble fiber, such as Guar gum and Psyllium, and microelements, such as selenium and magnesium, would impose a converse effect ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in routine clinical practice, dietary management is usually considered the cornerstone of any treatment for chronic constipation. Finite sample size and methods restrict the exploration of complex mechanisms linked to all kinds of foods, so current research mainly focuses on a small part of food ingredients, such as fiber and mineral water ( 5 ). Previous studies have confirmed that intake of low liquid, high dietary saturated fat would increase the constipation risk, while intake of soluble fiber, such as Guar gum and Psyllium, and microelements, such as selenium and magnesium, would impose a converse effect ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…KD should be used with caution, based on studies that report an increased risk of constipation in patients using this nutritional pattern, especially those over 70 years of age [ 138 ]. Finally, general indications suggested not to skip meals [ 139 ]; in this context, IF regimen should be avoided.…”
Section: Nutrition and Symptoms Related To Neuroendocrine Neoplasmsmentioning
confidence: 99%
“…Constipation, characterized by dry stools, prolonged defecation cycle, and defection difficulty, is one of the most common gastrointestinal disorders diagnosed in clinical practice, with a prevalence of 12%-19% worldwide (Bellini et al, 2021;Włodarczyk et al, 2021). Constipation decreases quality of life as patients often suffer from both physical symptoms and psychological distress (Włodarczyk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%